Relativistic coupled-cluster investigation of parity (P) and time-reversal (T) symmetry violations in HgF - Talukdar, Kaushik; Nayak, Malaya K.; Vaval, Nayana; Pal, Sourav (Journal of Chemical Physics, 2019)
We employ the Z-vector method in the four-component relativistic coupled-cluster framework to calculate the parity (P) and time-reversal (T) symmetry violating scalar-pseudoscalar nucleus-electron interaction constant (W-s), the effective electric field (E-eff) experienced by the unpaired electron, and the nuclear magnetic quadrupole moment-electron interaction constant (W-M) in the open-shell ground electronic state of HgF. The molecular frame dipole moment and the magnetic hyperfine structure (HFS) constant of the molecule are also calculated at the same level of theory. The outcome of our study is that HgF has a high value of E-eff (115.9 GV/cm), W-s (266.4 kHz), and W-M (3.59 x 10(33) Hz/e cm(2)), which shows that it can be a possible candidate for the search of new physics beyond the standard model. Our results are in good agreement with the available literature values. Furthermore, we investigate the effect of the basis set and the virtual energy functions on the computed properties. The role of the high-energy virtual spinors is found to be significant in the calculation of the HFS constant and the P,T-odd interaction coefficients. Published under license by AIP Publishing.